1989
DOI: 10.1002/jor.1100070213
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of slipped capital femoral epiphysis: Pathogenetic considerations

Abstract: Two normal proximal femoral growth plates and core biopsies from six patients with slipped capital femoral epiphysis (SCFE) were studied by electron microscopy. In these SCFE patients, chondrocytes from all the zones of the plate were frequently smaller than normal, more irregular in shape, and many of them were degenerating, with formation of matrix vesicles and cellular debris. Floccular electron-dense material, most likely abnormal proteoglycan, was present in the hypertrophic rough-surfaced endoplasmic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The resting zones of the epiphysis appeared to be relatively normal in SCFE [3][4][5][6], although some tissue samples showed clusters of numerous chondrocytes cells [5].…”
Section: Histological Changes In Scfementioning
confidence: 99%
See 1 more Smart Citation
“…The resting zones of the epiphysis appeared to be relatively normal in SCFE [3][4][5][6], although some tissue samples showed clusters of numerous chondrocytes cells [5].…”
Section: Histological Changes In Scfementioning
confidence: 99%
“…The proliferative and hypertrophic zones of the epiphysis in SCFE were widened compared with normal physis, and showed irregular columnar organisation with gradual loss of longitudinal septa and diminished number of chondrocytes in each column [3][4][5][6][7]. Interestingly, Adamczyk et al showed that apoptosis was increased throughout the physis in SCFE, in contrast with controls, where apoptosis was found only in the hypertrophic zone [8].…”
Section: Histological Changes In Scfementioning
confidence: 99%
“…In the PGs, another component of the extracellular matrix, we did not find any abnormalities—either in the morphology or in the distribution. Ippolito et al (1989) believed that the floccular electron-dense material present in the chondrocytes and in the matrix is caused by an altered production of PGs. However, our observations did not confirm this supposition.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported histological alterations of the growth plate in slipped capital femoral epiphysis (SCFE) (Kleinberg and Buchman 1936, Howorth 1941, 1949, Harris 1950, Lacroix and Verbrugge 1951, Ponseti and McClintock 1956, Wagner 1961, Taillard et al 1964, Consolo and Randelli 1971, Ippolito et al 1981, Agamanolis et al 1985a, Portigliatti Barbos et al 1985, Guzzanti et al 2003). To our knowledge, however, there have only been 3 ultrastructural studies that have considered the pathology of the slippage in SCFE (Mickelson et al 1977, Agamanolis et al 1985b, Ippolito et al 1989). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation